EFEKTIVITAS PENGGUNAAN GOOGLE CLASSROOM DALAM MATA PELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN (PJOK) DI KELAS XI IPA SMAN 1 BINTAN UTARA - Kevin Pratama; Agus Sulastio; Agus Prima Aspa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The problem in this research was due to the outbreak of the Corona virus (Covid-19) in Indonesia in early 2020. The government tried to prevent the spread of the Corona virus outbreak through the community activities on various aspects, including education, to limit. Because of this policy, schools all over Indonesia are implementing distance learning or drop off using Google Classroom media. The aim of this research was to "know the effectiveness of using Google Classroom in physical education, sports and health (PJOK) subjects in class XI IPASMAN 1 Bintan Utara". The population of this research were students of Class XI IPA SMAN 1 Bintan Utara using a purposeful sampling technique that collected 45 students. The techniques and tools used for data collection were questionnaires or questionnaires completed by students. Based on the data and discussion above, this study can be said that: the implementation of google classroom learning as a learning medium at SMA Negeri 1 Bintan Utara out of the indicators is quite effective as it has an average of 88.88%.Key Words: Efectiveness, Google Classroom, PJOK